A cultura informacional no processo de implementação da nova estrutura organizacional do sistema de bibliotecas da Universidade Federal da Paraíba - Silva, Josélia Maria Oliveira da (2012)
The paper analyzes the informational culture study on the implementation process of the new organizational structure from the Paraíba Federal University Libraries System. Our general aim is to analyze the implications of the informational culture into this system, as a helper element to the new organizational structure implementation. Methodologically, this research has an exploratory-descriptive nature, and a quantitative and qualitative approach. The ways used were characterized like a documental and field research. As researching tools we adopted the inquiry form, with open and closed questions; the semi-structured interview and the strict observation. The data was systematized into tables and frames. For to do the data analysis was adopted the content analysis technique associated with the data triangulation strategy. The obtained results indicate that the informational culture, as acting into the Libraries System, doesn t contributes to the implementation of the new organizational structure, in view of informational meanders doesn t demonstrate to exist equities into the informational behavior between the strategic and tactical management when adopted on the system focused. Results allow conclude that the sector libraries managers and the libraries system manager need to face the challenge of build together in a systematic, structured and participative way a possible informational culture to concatenate within this structure the formal and informal ways of communication. Determinant is to provide the information exchange and sharing to contribute with the organizational development to leverage their informational resources. For that, the team needs to know the informational processes and to institute policies that give sufficient possibilities the information management. Besides it, each manager, as a organizational leader, needs to form an holistic perception of the organization to use in a adequate way the necessary communication channels to the creation of a strong and coherent informational culture, in agree with the information unit goals to serve at an academic environment.